Obesity : epidemiology, pathophysiology, and prevention - Bagchi, Debasis, 1954-; Preuss, Harry G. (Boca Raton : CRC Press, 2013)
'The spread of obesity has been declared a worldwide epidemic by the World Health Organization (WHO). In fact, a new term, globesity, has been coined to describe the recent upsurge of overweight and obesity throughout the world's population. How severe is the problem? According to WHO, worldwide obesity has more than double since 1980. In 2008, 1.5 billion adults, 20 and older, were overweight [1]. Of these over 200 million men and 300 million women were obese. 65% of the world's population live in countries where overweight and obesity kills more people than underweight [1]. Furthermore, nearly 43 million children under the age of five were underweight in 2010 [1]'--
Includes bibliographical references and index.
Keywords: Obesity -- Epidemiology; Obesity -- Pathophysiology; Obesity -- epidemiology; Obesity -- physiopathology; Obesity